Comparison of Serum Zinc and Copper Concentrations in Females with Ovarian and Uterine Tumors - Hiba Ghmeedh Adhab; Liwaa Hussein Mahdi; Eman M. Al-Hilo (Journal of Medical Physics)
Background and Aims: Ovarian and uterine tumors are among the most serious gynecological diseases and the most common cause of mortality globally. In recent times, the role of trace elements in the onset and development of tumors has come under the review. This study aimed to assess the levels of Zn and Cu in the serum of female patients with benign and malignant uterine and ovarian tumors. Materials and Methods: One hundred and twenty-four women with benign and malignant ovarian and uterine tumors were eligible for the study. Blood samples were obtained and analyzed using flame-atomic absorption spectroscopy spectrometry in Najaf City, Iraq. Results: Serum zinc levels exhibited lower concentration (4.73 ± 1.92) in patients with malignant uterine tumors than those with benign uterine tumors (10.80 ± 1.87, P = 0.000). In contrast, the mean concentration of copper was higher in patients with malignant uterine tumors (110.37 ± 20.05 vs. 103.75 ± 14.34, P = 0.063). The serum zinc concentrations (12.73 ± 5.34 vs. 8.90 ± 2.77, P = 0.001) were higher in patients with malignant ovarian tumors. Furthermore, we found the mean serum copper levels in patients with benign ovarian tumors decreased significantly from (101.86 ± 15.44 to 86.77 ± 21.55, P = 0.002) in female patients with malignant ovarian tumors group. Conclusions: Serum concentrations of copper and zinc increased in some study groups and declined in others. The examination of serum trace element concentrations in patients with ovarian and uterus tumors would provide us with insight into a better understanding of the pathogenesis of the tumors and also to distinguish between them.